2023
DOI: 10.1186/s13020-023-00819-4
|View full text |Cite
|
Sign up to set email alerts
|

Gegen Qinlian decoction (GQD) inhibits ulcerative colitis by modulating ferroptosis-dependent pathway in mice and organoids

Xue Wang,
Jianye Quan,
Chengkui Xiu
et al.

Abstract: Background Gegen Qinlian decoction (GQD) is a classic prescription for treating ulcerative colitis (UC) in traditional Chinese medicine. However, the therapeutic mechanism has not been fully clarified. Purpose In the present study, we aimed to evaluate the role of ferroptosis-mediated IEC death in UC treated mice with GQD by using DSS-induced a colitis mouse model and RSL3-induced ferroptosis in intestinal organoids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Activating this signal can reverse it . In addition, increasing GPX4 activity can effectively improve colon histological damage and intestinal epithelial barrier dysfunction and reshape intestinal microecology (Wang et al, 2023). In addition, experiments using DSS-induced NCM460 cells revealed that activation of the Nrf2-GPX4 signaling pathway could effectively protect intestinal epithelial cells from Ferroptosis injury and alleviate UC (Dong et al, 2021).…”
Section: Ferroptosismentioning
confidence: 97%
“…Activating this signal can reverse it . In addition, increasing GPX4 activity can effectively improve colon histological damage and intestinal epithelial barrier dysfunction and reshape intestinal microecology (Wang et al, 2023). In addition, experiments using DSS-induced NCM460 cells revealed that activation of the Nrf2-GPX4 signaling pathway could effectively protect intestinal epithelial cells from Ferroptosis injury and alleviate UC (Dong et al, 2021).…”
Section: Ferroptosismentioning
confidence: 97%
“…Of note, the role of GQD in inducing SCFAs was also observed in the treatment of type 2 diabetes, it could increase the abundance of probiotics and SCFA-producing bacteria such as Bifidobacteria [ 76 ]. Wang et al [ 77 ] found that GQD could suppress UC by modulating the ferroptosis pathway in mice. Under this circumstance, GQD-induced production of SCFAs in the intestine might play an important regulatory role in the suppression of UC-associated conditions.…”
Section: Traditional Medicine and Their Derivatives Act On Scfas To A...mentioning
confidence: 99%